Instrumentation : devices and systems - Rangan, C. S.; Sarma, G. R.; Mani, V. S. V. (New Delhi : Tata McGraw-Hill Publishing Company Limited, 1998)
This book is its second edition incorporates the most recent breakthroughs in the field of instrumentation. It is now throughly revised in view of the onset of many solid state devices with high accuracy, as well as the availability of latest electronic chips for faster data collection, with full compatibility for microprocessor interfacing.
Keywords: ENGINEERING INSTRUMENTS; ELECTRONIC INSTRUMENTS; ELECTRONIC APPARATUS AND APPLIANCES; PHYSICAL MEASUREMENTS